Penanaman Nilai-Nilai Ahlussunnah Wal Jama’ah An Nahdliyah Melalui Pendidikan Agama Islam di Sekolah - Suwaibatul Aslamiyah, Siti; Arifianti, Rizqi (Darajat: Jurnal Pendidikan Agama Islam, 2022)
The values of Ahlussunnah Wal Jamaah An-Nahdliyyah are very in line with Indonesian Islam, because the values of Ahlussunnah Wal Jamaah An-Nahdliyyah are considered to provide mashlahah for the formation of character and morals of the Indonesian nation, thereby increasing the Indonesian Islamic community who adheres to the teachings of the Qur'an. and Hadith and have values that are suitable to be taught and instilled in students in order to form character and morality.Through religious education in schools, the values of Ahlussunnah Wal Jamaah AnNahdliyyah which teach a diverse mindset and avoid extremism (at-tawassut), intelligence, honesty, and justice (al-I'tidal), tolerance (at-tasamuh), and a balanced approach in khidmah (at-tawazun) and preventing evil deeds and encouraging good deeds (amar ma'ruf nahi munkar), given by going through three stages namely; Value Transformation (knowing stage), Value Transaction (doing stage), and Value transinternalization (being stage).